Egyptian Ammiyah Speaking Training in the Muhammadiyah Darul Arqom Islamic Boarding School, Depok - akbar, Doni Wahidul Akbar; Abidin, Zainul (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Arabic has two dialects, namely Arabic Fusha and Arabic Ammiyah. Arabic Fusha is the language used in the Al-Quran, al-Hadith, and scientific writings. Arabic Fushahh has become an international language that was inaugurated on December 18, 1973, by UNESCO (United Nations Education, Scientific, and Cultural Organization). Arabic fusha (standard variety) is the language used in the Qur'an, official situations, composing poetry, writing prose, and expressions of thought (scientific writings). Arabic Fusha is also commonly used as the official language of instruction on campuses or Islamic Universities in the Middle East. Meanwhile, Arabic 'Ammiyah (non-standard variety) is a variety of languages ​​used for ordinary daily affairs. In Arab countries stretching from the Persian Gulf to the Mediterranean Sea, there are various dialects of 'Ammiyah (non-standard variety), each with different phonetics, vocabulary, and structure. The Arabic 'âmiyah is different from the Arabic fushâ. This difference occurs in phonetic aspects and choice of words. At the level of choice of words, for example, ثلاثة أسابي مدة إقامتي هنا (muddatu iqâmtî huna tsalâtsatu asâbî’: I’m here for three weeks). This sentence in the 'âmiyah of Egypt is expressed أنا هنا ثلاثة أسابي (ana hina talâtasâbi’), and in Gulf Arabic it is expressed مدة ثلاثة أسابي أنا هنا (ana hina mudah tsalâtha asâbi’), whereas in Levantine Arabic it is expressed أنا هون لثلاثة أسابيع (ana hoon li talâti esâbi’). The lack of knowledge of students in Indonesia about the Ammiyah language has an impact on the need for training for students with the theme